The Effect Of Spiritual Emotional Freedom Technique (SEFT) On Psychological Well-Being In Patients Type 2 Diabetes Mellitus - Nurlela Hi Baco; Bayu Dwisetyo; Rifky Mokoginta (Sean Institute, 2023)
Background Diabetes Type 2 long-term treatment will affect a person's psychology. Type 2 DM patients who have low Psychological Well-Being result in low self-care. So Spiritual Emotional Freedom Technique (SEFT) is needed because this therapy uses spiritual elements for psychological and physical problems caused by emotional or psychomatic causes. The purpose of the study was to determine the effect of Spiritual Emotional Freedom Technique (SEFT) on Psychological Well-Being in Type 2 Diabetes Mellitus Patients in Tewaan Village, Bitung City. The research method used is Quasy Experiment with One Group Pre-Post Test design. The sample in this study 12 respondents using accidental sampling technique. The research instrument used is a questionnaire. Then the data collected was processed and analyzed using the Wilcoxon statistical test with a significance level (α) = 0.05. Research Results From the Wilcoxon statistical test, it was found that the P Value = 0.001 with a significance of <0.05, which means Ha is accepted and Ho is rejected. The conclusion is that there is the influence of Spiritual Emotional Freedom Technique (SEFT) on Psychological Well-Being in Type 2 Diabetes Mellitus Patients in Tewaan Village, Bitung City. Suggestions are expected to improve Psychological Well-Being in People with Type 2 Diabetes Mellitus in the Tewaan Village, Bitung City.